Hydrodynamic impact in an attempt to assess the possibility of analyzing the causes of damage to asphalt concrete pavement - Witold Paleczek (Przegląd Komunikacyjny)
Abstract: The phenomenon of hydrodynamic impact was presented as an attempt to assess the possibility of including this phenomenon as one of the main caused leading to the formation of damage to the asphalt concrete pavement. This phenomenon occurs regardless of the season. Pavement damage caused by the freezing of water solutions in the mesh cracks and line cracks is widely known and, as well as swelling ice in clay soil, are among the main caused of pavement damage. It was justified that the hydrodynamic impact caused by the wheels of the front a then the rear axle of the vehicle with elastic tires causes the formation of wave phenomena that may lead to exceeding the material effort. Exceeding the permissible stresses in the formant range of the resonant frequency may lead to the loss of cohesion and load capacity of this material.)